Maintenance of subsynaptic myonuclei number is not driven by neural input - Ruiz, Lloyd P.; Macpherson, Peter C.; Brooks, Susan V. (Frontiers in Physiology, 2023)
The development and maintenance of neuromuscular junctions (NMJ) are supported by a specialized population of myonuclei that are referred to as the subsynaptic myonuclei (SSM). The relationship between the number of SSM and the integrity of the NMJ as well as the impact of a loss of innervation on SSM remain unclear. This study aimed to clarify these associations by simultaneously analyzing SSM counts and NMJ innervation status in three distinct mouse models of acute and chronic NMJ disruption. SSM were identified using fluorescent immunohistochemistry for Nesprin1 expression, which is highly enriched in SSM, along with anatomical location beneath the muscle fiber motor endplate. Acute denervation, induced by surgical nerve transection, did not affect SSM number after seven days. Additionally, no significant changes in SSM number were observed during normal aging or in mice with chronic oxidative stress (Sod1-/-). Both aging WT mice and Sod1-/- mice accumulated degenerating and denervated NMJ in skeletal muscle, but there was no correlation between innervation status of a given NMJ and SSM number in aged or Sod1-/- mice. These findings challenge the notion that a loss of SSM is a primary driver of NMJ degradation and leave open questions of the mechanisms that regulate SSM number as well as the physiological significance of the precise SSM number. Further investigations are required to define other properties of the SSM, such as transcriptional profiles and structural integrity, to better understand their role in NMJ maintenance.